Development of a WiMAX processor by using a CPLD - Sato, Tomoaki; Moungnoul, Phichet; Fukase, Masa Aki (My University, 2010)
WiMAX (Worldwide Interoperability for Microwave Access) is one of the standards for high-speed wireless communications. The development cycle of a WiMAX processor is short because a transmission rate of a WiMAX system improves gradually. To keep using it even when the speed improves, there is a method of development that uses a processor that can be a reconfiguration of a circuits. In this paper, a mobile WiMAX processor by using a CPLD (Complex Programmable Logic Device) is proposed. Because wave-pipeline technique is used, the problem of processing speed is canceled. The authors evaluate wave-pipelined circuits which WiMAX processor needs on a CPLD. It is made clear that wave-pipeline technique is effective in the circuits on the CPLD.
Keywords: CPLD; FPGA; Gate-level simulation; Wave-pipelining; WiMAX